Strategi Pengelolaan Sumber Daya Perikanan Berkelanjutan di Era Modern - Narwadan, Theresia; Kubela, Salomina; Tamalene, Arisma (CV. SINAR HOWUHOWU, 2024)
The sustainable management of fishery resources has become a significant challenge in the modern era due to overfishing, habitat degradation, and illegal fishing activities. This study aims to identify effective management strategies through modern technological approaches and community-based frameworks. The research methodology employs a mixed-methods approach, encompassing interviews, questionnaires, field observations, and secondary data analysis across several strategic coastal regions in Indonesia. The findings reveal that utilizing technologies such as the Vessel Monitoring System (VMS) and data-sharing applications enhances the efficiency of fisheries management. Community-based approaches have also proven effective in preserving ecosystems and improving fishers' welfare. Moreover, regulations based on fish stock data are critical elements in ensuring the sustainability of the sector. This study concludes that synergy between technology, inclusive policies, and community participation is the key to achieving sustainable fishery resource management in the modern era.